2019
DOI: 10.2147/ott.s219111
|View full text |Cite
|
Sign up to set email alerts
|

<p>Communication Of Cancer Cells And Lymphatic Vessels In Cancer: Focus On Bladder Cancer</p>

Abstract: Bladder cancer is one of the most commonly diagnosed cancers worldwide and causes the highest lifetime treatment costs per patient. Bladder cancer is most likely to metastasize through lymphatic ducts, and once the lymph nodes are involved, the prognosis is poorly and finitely improved by current modalities. The underlying metastatic mechanism for bladder cancer is thus becoming a research focus to date. To identify relevant published data, an online search of the PubMed/Medline archives was performed to locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 184 publications
(195 reference statements)
0
5
0
Order By: Relevance
“…Bladder cancer is one of the most common urological carcinomas in the world. [1][2][3] It is reported that the incidence of bladder cancer is still increasing. 4,5 Furthermore, bladder cancer presents a high recurrence rate and mortality rate because of the absence of typical symptoms at the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer is one of the most common urological carcinomas in the world. [1][2][3] It is reported that the incidence of bladder cancer is still increasing. 4,5 Furthermore, bladder cancer presents a high recurrence rate and mortality rate because of the absence of typical symptoms at the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…In Guanghzou, an economically developed city in China, CRC heredity clinics have been set up to improve the prevention and treatment of relatives of patients with CRC since July 2015 22 . In hereditary CRC clinics, oncology nurses will screen out high-risk FDRs based on the information about patients and family members 34 . Disease-related lectures and screening information counseling are provided for FDRs; however, our data indicate that their screening behavior has not demonstrably improved.…”
Section: Discussionmentioning
confidence: 88%
“…At present, determination of how high-risk family members can be identified as early as possible has become an important issue. In Guanghzou, an economically developed city in China, CRC heredity clinics have been set up to improve the prevention and treatment of relatives of patients with CRC since July 2015 22 . In hereditary CRC clinics, oncology nurses will screen out high-risk FDRs based on the information about patients and family members 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Mukherjee et al (2018 ) revealed that intratumoral CD56 + NK cells were frequent in lymphoid tissues and associated with better prognosis, while CD56 − NK cells were the opposite. Meanwhile, a systemic review conducted by Wu et al (2019 ) indicated that lymphangiogenesis and lymph node invasion might influence cancer cell spread. Also, lymph vessels could affect tumor immunity (for instance, transporting antitumor CD8 + T cells) to hamper localized tumor tissues playing a dual role in the tumor environment.…”
Section: Discussionmentioning
confidence: 99%